2019
DOI: 10.1016/j.bbmt.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Development of and Progression of Hepatic Veno-Occlusive Disease/Sinusoidal Obstruction Syndrome

Abstract: A B S T R A C T Veno-occlusive disease, also known as sinusoidal obstruction syndrome (VOD/SOS), is a potentially life-threatening complication of allogeneic or autologous hematopoietic stem cell transplantation (HSCT) most commonly associated with high-intensity chemotherapies. The development of VOD/SOS may be rapid and unpredictable, and the importance of identifying risk factors to facilitate prompt diagnosis and timely treatment has become increasingly recognized. The reporting of new retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 93 publications
(179 reference statements)
0
102
2
1
Order By: Relevance
“…Further studies also showed that increased vWF levels can be used as a non‐invasive predictor of portal hypertension, decompensation and mortality in patients with liver cirrhosis 19,33 . It has been known that the pathogenesis of sinusoidal obstructive syndrome, also termed veno‐occlusive disease, involves direct toxic injury to the sinusoidal endothelial cell that triggers endothelial activation and damage in the setting of bone marrow transplantation, especially haematopoietic stem cell transplantation, and the use of oxaliplatin‐based adjuvant or neoadjuvant regimens to treat patients with liver metastatic colorectal cancer 34–36 . The increase of biomarkers of endothelial injury such as vWF can be used to predict sinusoidal obstructive syndrome in bone marrow transplant patients 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies also showed that increased vWF levels can be used as a non‐invasive predictor of portal hypertension, decompensation and mortality in patients with liver cirrhosis 19,33 . It has been known that the pathogenesis of sinusoidal obstructive syndrome, also termed veno‐occlusive disease, involves direct toxic injury to the sinusoidal endothelial cell that triggers endothelial activation and damage in the setting of bone marrow transplantation, especially haematopoietic stem cell transplantation, and the use of oxaliplatin‐based adjuvant or neoadjuvant regimens to treat patients with liver metastatic colorectal cancer 34–36 . The increase of biomarkers of endothelial injury such as vWF can be used to predict sinusoidal obstructive syndrome in bone marrow transplant patients 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers (70) have been proposed for VOD/SOS diagnosis and/or prevention; they are markers of hemostasis and coagulation such as plasminogen activator inhibitor 1 (PAI-1) or other markers of endothelial injury, such as elevated levels of von Willebrand factor, thrombomodulin, soluble intercellular adhesion molecule 1, suppressor of tumorigenicity 2, angiopoietin 2, hyaluronic acid (HA), or markers of inflammation [interleukin 6 (IL-6), IL-10, CD97].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…The authors did not include pretransplant therapies impacting on VOD/SOS, so the applicability of this model to patient receiving either gemtuzumab ozogamicin or inotuzumab ozogamicin is still unknown. Prospective validation of risk factors is yet to be completed and needs further assessment to provide a more precise estimation of the magnitude of each risk factor (70).…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…Reports examining such features often utilise odds ratio data to characterise the degree of risk for each factor associated with this multi‐organ syndrome (Table I). Most importantly, prior and/or current liver dysfunction, prior intense chemo and/or radiotherapy and abnormal busulfan pharmacokinetics have been major factors in the past for increasing the risk of VOD post‐HCT (Dalle & Giralt, 2016; Hwang et al , 2016; Yakushijin et al , 2016; Corbacioglu et al , 2019; Faraci et al , 2019). Importantly, administering high‐dose busulfan prior to high‐dose cyclophosphamide prior to HCT significantly increases the levels of cyclophosphamide metabolites, including hydroxycyclophosphamide and carboxyethylphosphoramide, which is significantly associated with an increased risk of SOS/VOD.…”
Section: Risk Factors Associated With the Development Of Sos/vod Follmentioning
confidence: 99%